Experimental Investigation on Fatigue and Low Temperature Properties of Asphalt Mixtures Designed with Reclaimed Asphalt Pavement and Taconite Aggregate. Issue 3 (March 2019) - Moon, Ki Hoon; Cannone Falchetto, Augusto; Wang, Di; Kim, Yun Su
Using reclaimed asphalt material for rehabilitation and construction of new asphalt pavements is currently a common practice not only in view of the economic benefits associated with this process but also because of the reduced exploitation of natural resources. For this reason, road authorities have implemented recommendations and guidelines to regulate the use of reclaimed asphalt pavement (RAP) and other recycled materials such as industrial by-products. Nevertheless, the combined use of different recycled materials is not commonly addressed. In this paper, the effect of adding RAP and taconite (a mining by-product) on fatigue and low temperature properties of asphalt mixture was investigated with two different testing geometries: indirect tensile (IDT) and semi-circular bending (SCB). Fatigue behavior, creep stiffness, relaxation modulus, low temperature fracture energy, and fracture toughness were also evaluated, computed, and then compared. A more brittle behavior was observed for mixture prepared with RAP material, however, the mechanical performance was not significantly different for mixtures containing 20% RAP alone and in combination with 50% taconite compared with conventional asphalt mixtures designed with virgin material. This was not the case when RAP content was increased up to 50%, showing a substantially poorer response both in terms of fatigue and low temperature characteristics and suggesting the RAP had a dominant effect. The present exploratory research seems to support the idea of combining RAP and different industry by-products, such as taconite, as long as the RAP content is kept below a specific threshold.